THE EFFECT OF MARKET SENSING CAPABILITY (SENSING MARKETING) AND PRODUCT INNOVATION CAPABILITY ON MARKET PENETRATION IN MARKETING PERFORMANCE - Dwi Bhakti Iriantini (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study is to analyze the effect of market sensing capabilities and product innovation capabilities on marketing performance through market penetration as a bridge to solve gaps regarding the impact of product innovation capabilities on marketing performance. Data is collected empirically from the owner of Batik UMKM (Micro, Small and Medium Enterprises) in Bangkalan Regency, Madura, East JavaDistribusi Sampel diberikan kepada 120 dengan menggunakan teknik sample random sampling . Model persamaan struktural (SEM) dengan perangkat lunak AMOS digunakan untuk menguji model dan hipotesis penelitian. The results of data analysis show that the research model has good fit. Five hypotheses are proposed and all hypotheses can be proven, especially the ability of market penetration in bridging the capabilities of product innovation and marketing performance. To get market penetration in marketing performance by looking at market sensing capabilities, to get good marketing performance also by looking at the capabilities of product innovation without going through market penetration